A Bin and a Bulk Microphysics Scheme Can Be More Alike Than Two Bin Schemes. (3rd March 2023) - Hu, Arthur Z.; Igel, Adele L.
Abstract: Bin and bulk schemes are the two primary methods to parameterize cloud microphysical processes. This study attempts to reveal how their structural differences (size‐resolved vs. moment‐resolved) manifest in terms of cloud and precipitation properties. We use a bulk scheme, the Arbitrary Moment Predictor (AMP), which uses process parameterizations identical to those in a bin scheme but predicts only moments of the size distribution like a bulk scheme. As such, differences between simulations using AMP's bin scheme and simulations using AMP itself must come from their structural differences. In one‐dimensional kinematic simulations, the overall difference between AMP (bulk) and bin schemes is found to be small. Full‐microphysics AMP and bin simulations have similar mean liquid water path (mean percent difference <4%), but AMP simulates significantly lower mean precipitation rate (−35%) than the bin scheme due to slower precipitation onset. Individual processes are also tested. Condensation is represented almost perfectly with AMP, and only small AMP‐bin differences emerge due to nucleation, evaporation, and sedimentation. Collision‐coalescence is the single biggest reason for AMP‐bin divergence. Closer inspection shows that this divergence is primarily a result of autoconversion and not of accretion. In full microphysics simulations, lowering the diameter threshold separating cloud and rain category in AMP from 80 $80$ to 50 μ m $50\, μ m$ reduces the largest AMP‐bin difference to ∼10%, making the effect of structural differences between AMP (and perhaps triple‐moment bulk schemes generally) and bin even smaller than the parameterization differences between the two bin schemes. Plain Language Summary: There are two primary ways to predict how clouds form and evolve. In a model grid box, bulk schemes typically predict the evolution of just the total number and mass of cloud droplets, whereas bin schemes not only keep track of total amount but also the number of droplets of different sizes. Bulk schemes are more computationally efficient than bin schemes, but bin schemes are usually assumed to be more accurate. This study aims to reveal how such differences affect their prediction of clouds. Our results show that small droplets colliding and combining to form raindrops is the only process that leads to large differences between bin and bulk schemes. Other individual processes, including droplet activation, condensation, evaporation, and sedimentation, contribute substantially less to differences between the two schemes. These results suggest that the advantages of using a bin scheme may not be as large as previously thought. Key Points: Bulk and bin microphysics schemes with the same parameterizations simulate clouds more similarly than those simulated by two bin schemes Substantial differences between bin and bulk schemes are found only for collisions; they are reduced with a lower cloud‐rain size boundary The advantages of using a bin scheme rather than a bulk scheme for microphysics may not be as large as previously thought